'Be active, eat right', evaluation of an overweight prevention protocol among 5-year-old children: design of a cluster randomised controlled trial - Veldhuis Lydian; Struijk Mirjam K; Kroeze Willemieke; Oenema Anke; Renders Carry M; Bulk-Bunschoten Anneke MW; HiraSing Remy A; Raat Hein (BMC, 2009)
Abstract Background The prevalence of overweight and obesity in children has at least doubled in the past 25 years with a major impact on health. In 2005 a prevention protocol was developed applicable within Youth Health Care. This study aims to assess the effects of this protocol on prevalence of overweight and health behaviour among children. Methods and design A cluster randomised controlled trial is conducted among 5-year-old children included by 44 Youth Health Care teams randomised within 9 Municipal Health Services. The teams are randomly allocated to the intervention or control group. The teams measure the weight and height of all children. When a child in the intervention group is detected with overweight according to the international age and gender specific cut-off points of BMI, the prevention protocol is applied. According to this protocol parents of overweight children are invited for up to three counselling sessions during which they receive personal advice about a healthy lifestyle, and are motivated for and assisted in behavioural change. The primary outcome measures are Body Mass Index and waist circumference of the children. Parents will complete questionnaires to assess secondary outcome measures: levels of overweight inducing/reducing behaviours (i.e. being physically active, having breakfast, drinking sweet beverages and watching television/playing computer games), parenting styles, parenting practices, and attitudes of parents regarding these behaviours, health-related quality of life of the children, and possible negative side effects of the prevention protocol. Data will be collected at baseline (when the children are aged 5 years), and after 12 and 24 months of follow-up. Additionally, a process and a cost-effectiveness evaluation will be conducted. Discussion In this study called 'Be active, eat right' we evaluate an overweight prevention protocol for use in the setting of Youth Health Care. It is hypothesized that the use of this protocol will result in a healthier lifestyle of the children and an improved BMI and waist circumference. Trial registration Current Controlled Trials ISRCTN04965410